Overview of Salvia miltiorrhiza as a Potential Therapeutic Agent for Various Diseases: An Update on Efficacy and Mechanisms of Action - Inyong Jung; Hyerin Kim; Seongcheol Moon; Hyuk Lee; Bonglee Kim (MDPI AG, 2020)
Salvia miltiorrhiza Bunge (S. miltiorrhiza) is a medicinal herb that has been used for the treatment for various diseases such as cardiovascular and cerebrovascular diseases in East Asia including Korea. Considering its extensive usage as a therapeutic agent for multiple diseases, there is a need to review previous research regarding its therapeutic benefits and their mechanisms. Therefore, we searched PubMed and PubMed Central for articles reporting its therapeutic effects on certain disease groups including cancers, cardiovascular, liver, and nervous system diseases. This review provides an overview of therapeutic benefits and targets of S. miltiorrhiza, including inflammation, fibrosis, oxidative stress, and apoptosis. The findings on multi-functional properties of S. miltiorrhiza discussed in this article support the efficacy of S. miltiorrhiza extract on various diseases, but also call for further research on the multiple mechanisms that mediate its therapeutic effects.